Development of the single-setup milling process model of the shaft support necks and cams - Kalchenko, Vitalii; Kalchenko, Volodymyr; Sira, Natalia; Kalchenko, Olga; Vynnyk, Volodymyr; Kalchenko, Dmytro; Morochko, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2020)
Three-dimensional geometrical modeling of the processes of allowance removal and shaping of support necks and cams of camshafts when milling with crossed axes of the tool and part is proposed. Single-setup milling of camshafts, which are widely used in automotive, tractor, shipbuilding and other industries, is carried out by a cutter with crossed axes of it and the part. The rotation angle of the cutter is selected from the condition of providing the required roughness of the treated surface and is regulated by the feed. At the same time, high processing productivity is provided by an increase in camshaft speed. A method of milling support necks and cams is developed, where the processing is carried out by a cutter, the height of which is less than the lengths of the processed surfaces. When processing the passage, the main allowance is removed by the end face of the quadrangular roughing carbide plate, and the finishing is carried out by the unloaded periphery of the cermet finishing plate. This allowance distribution increases the productivity and accuracy of processing, and the ability to rotate the roughing plate saves material and reduces the cost of processing. In the process of milling the curved surface of the camshaft cam, the depth of cut along the machined profile is always greater than the value of the removed allowance. This causes a decrease in the accuracy and productivity of processing. In order to eliminate this problem, it is proposed to stabilize the depth of cut and feed along the contour with uneven rotation of the part. The uniformity of the depth of cut and feed along the curved contour of the cam is achieved by simultaneous vertical and transverse movements of the cutter and uneven rotation of the camshaft. When milling the curved surface of the cam, the center of which does not coincide with the camshaft center, there is an uneven rotation of the latter and synchronous vertical and transverse movement of the cutter. When machining the cam section, the center of which coincides with the camshaft center, the cutter is given only rotation